DEMONSTRATION APPLICATION METHOD FOR IMPROVED MOTION NUSANTARA DANCE CLASS SDN 104 PEKANBARU - Fitriyanti, Devy Fitriyanti Devy; Antosa, Zariul Antosa Zariul; Kurniaman, Otang Kurniaman Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The background of this research is the lack of knowledge of teachers in learning the material master , no master of dance movement archipelago other areas and children do not know about other areas of the archipelago dance movement . This research was conducted with the aim to improve the ability of the archipelago dance with Learning Method Demonstration . Research findings show an increase in value - average ability to dance dance dance nusnatara especially tor - tor with preliminary data was 41.9 , an increase in the first cycle of 50.19 ( enough ) of the results of the initial data . In the assessment results kekampuan archipelago dance ( dance tor - tor ) second cycle value - average students increased to 71.2 ( capable ) . In the assessment of dance ability tor - tor the third cycle value - average students increased to 83.1 ( very poor). Activity teacher at the first meeting of the first cycle of 60 % with enough categories , increased in the second meeting rose to 70 % in both categories . At the first meeting of the second cycle increased by 80 % with good category , then at the second meeting rose to 85 % in both categories . At the first meeting of the third cycle increased to 90 % , increased in the second meeting be 95 % with a very good category . Average - average student activity in the first cycle of 50 % with the first peretmuan enough categories , increased in the second peretemuan 55 % with sufficient category . At the first meeting of the second cycle to 60 % with sufficient category , then at the second meeting of the second cycle increased to 70 % in both categories . At the first meeting of the third cycle of 90 % increase in the second meeting to 95 % . This shows that the application of the method can improve the ability of dance demonstration archipelago fifth grade students of SDN 104 Pekanbaru . Thus the hypothesis peneletian proven .Keywords : Demonstration , Dance Archipelago